Securing Public Trust Through Blockchain Integration: The Case of the National Police Clearance System in the Philippines - Fabro, Jhoanna Gracia M; Reyes, Solitaire M; Fabro, Arvin B; Gelacio, Roque Q; Reyes, Gary A; Train, Cedric G; Tanigue, Yolanda G; Dausan, Alrien F (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study examined the use of blockchain technology in the PNP National Police Clearance System (NPCS) to improve public trust. It first assessed trust in the current Relational Database Management System (RDBMS) based on availability, security, immutability, and transparency. Using an explanatory sequential method, the research surveyed 950 applicants and 175 end-users, and conducted 20 key informant interviews. Findings showed that while the public generally trusts the RDBMS (Availability M=3.25; Security M=3.32; Immutability M=3.29; Transparency M=3.22), they also viewed challenges as serious (Availability M=2.95; Security M=2.83; Immutability M=2.79; Transparency M=2.84). Issues included limited access, weak security, data integrity problems, lack of history logs, and poor control mechanisms. Blockchain technology was recommended as an alternative (Availability M=3.18; Security M=3.23; Immutability M=3.27; Transparency M=3.21). Statistical tests revealed significant differences based on awareness, gender, occupation, application purpose, and location. Regression showed a low dependency of blockchain on RDBMS (r²=0.27), but a moderate correlation between the two (0.52, t=16.75). Overall, the study recommends adopting blockchain in the NPCS to strengthen public trust.